Enhancing the E-Commerce Experience: Analysing the Impact of Convenience, Security, and Website Features on Consumer Purchasing Behaviour - Giridharan, K. S. (International Journal of Psychosocial Rehabilitation, 2015)
Online shopping, a cornerstone of modern e-commerce, is not just a medium for transactions but a significant aspect of daily life for consumers. This study delves into the dynamics of consumer interaction with online shopping platforms, emphasising the growing prevalence of digital marketplaces in purchasing habits and information acquisition. Our exploratory factor analysis reveals that the critical determinants of consumer behaviour include convenience, advanced website features, robust security measures, and the efficiency of the shopping experience. Regression analysis further corroborates these factors’ positive and substantial influence on consumer purchase decisions at a one percent significance level. Website features and security protocols are pivotal in forging consumer trust and shaping shopping behaviour. Additionally, personalised shopping experiences emerge as a critical driver of customer satisfaction, suggesting online retailers harness personalisation to enhance user engagement. The abstract advocates for online retailers prioritising a user-centric approach in website design, ensuring simplicity, user-friendliness, and convenience. It also underscores the importance of efficient delivery services as a critical component of the consumer-retailer relationship. Looking ahead, the paper suggests that retailers must adapt to the rapidly evolving landscape of consumer expectations and technological innovations, with ongoing research imperative to stay ahead in the digital marketplace.